CHROMOSOMAL COMPLEMENT AND DISTRIBUTION OF A WOLF (CANIS LUPUS L.) IN THE NORTH CAUCASUS - R. I. Dzuev; M. V. Suhomesova; V. N. Kanukova (Юг России: экология, развитие, 2014)
The chromosomal complement of a Canis lupus L. in the North Caucasus is described for the first time in this work. The data about modern distribution of a wolf in this territory taking into account mountain ecosystems of caucasus is also cited. The data about number of Canis lupus L., on its regulation in natural and anthropogenic ecosystems of the North Caucasus is cited.